THE EFFECT OF GROUP GUIDANCE WITH ROLE PLAYING TECHNIQUES ON INCREASING STUDENT LEARNING MOTIVATION - Dimas; Muhammad Ferdiansyah; Yulianti (Jurnal Kopendik, 2026)
This study aims to determine the effect of group guidance services with role playing techniques on increasing student learning motivation at SMA Negeri 4 Jambi City. Low student learning motivation is still found, characterized by a lack of active participation, learning discipline, and achievement motivation. This study uses a quantitative approach with a one group pretest-posttest experimental design. The research subjects were 10 students of class XI F9 who were selected by purposive sampling. Data were collected using a 25-item learning motivation questionnaire, using a Likert scale and analyzed using SPSS 27. The results of the instrument test in the initial pre-test obtained a score of 71.6, included in the moderate category with a score range of 50-66, in the post-test increased to 100.9, included in the very high category with a score range of 84-100.